The Prevention and Reduction of the Bullwhip Effect by Electronic Data Interchange and Collaborative Forecasting - Bahija Jardini (European Scientific Journal, ESJ, 2021)
The bullwhip effect is a phenomenon of curious amplification of variations in demand as one moves away from the final customer. Popularized by Lee and al., (1997), the bullwhip effect has negative consequences on all actors in the supply chain because it generates considerable loss of profits: Too much stock, loss of sales, poor customer service, insufficient quality and multiple disruptions of flow and organization. To prevent and reduce the bullwhip effect, various tools are recommended. The Electronic Data Interchange (EDI) is among the most important given its impact on accelerating information sharing throughout the supply chain. This paper aims to shed light on the role of EDI, VMI (Vendor-managed inventory) and CPFR (collaborative planning forecasting and replenishment) in the prevention and reduction of the bullwhip effect in the supply chain.